PHYSICAL ACTIVITY, BODY COMPOSITION, AND ANTHROPOMETRIC PROFILE OF SELECTED SUBJECTS OF THE RIO DO SINOS VALLEY, RIO GRANDE DO SUL (Fiep Bulletin - online, 2015)
This research had the objective to identify the level of physical activity (LPA) and the anthropometric profile and body composition of selected subjects of the Vale do Sinos, RS. The sample of the study was composed of 187 subjects with age ranging from 18 to 80. The IPAQ and the anthropometric assessment were used to collect the data. The ANOVA and Tukey post-hoc test were used to identify the differences between the variables at 0.05 level. It was observed a prevalence of 17.6% of the subjects (n=33) classified as very active, 26.8% (n=50) sufficiently active, and 55.6% (n=104) insufficiently active. A significant difference (p=0.002) was found between the LPA and the time the subjects stayed seated in a day. In relation to Body Mass Index, there was a prevalence of 51.1% (n=94) of the subjects classified as normal weight, 33.7% (n=62), overweight, and 15.2% (n=28), obese. The waist and hip circumferences and the body adiposity presented the same significant difference (p=0.000). It was concluded that there was a higher prevalence of subjects insufficiently active and the Body Mass Index can also be considered a simple and adequate estimator for the calculation of the body fat percentage in population studies.
Keywords: Physical activity. Body mass. Anthropometry. Body Mass Index.